The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1128/jvi.01014-23
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of novel simian adenoviruses from macaques for development of a vector for human gene therapy and vaccines

Wendong Lan,
Lulu Quan,
Yiqiang Li
et al.

Abstract: Both human and non-human simian adenoviruses (HAdVs and SAdVs, respectively) have been used as gene therapy and vaccine vectors. The high prevalence of HAdVs and the neutralizing antibodies associated with prior infection, may limit HAdV-based vector use in human subjects. To overcome this drawback, a vector derived from a newly isolated and characterized macaque adenovirus was constructed. SAdVs (33.9%) were screened from 115 SAdV fecal samples collected at a zoological park. One novel SAdV was isolated and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 84 publications
(104 reference statements)
0
2
0
Order By: Relevance
“…Low biocontainment requirements for production; v. Ability to promote durable and robust humoral and cellular immune response [ 41 ]. Researchers have developed several novel adenoviral vectors for gene delivery, such as simian adenoviruses [ 26 ], human adenovirus type 4 (Ad4) [ 42 ], human adenovirus type 35 [ 43 ] (Ad35) vectors, and chimpanzee adenovirus type 68 (cAd68) [ 44 ]. Previous studies have demonstrated that these novel adenovirus vectors mediate the diverse immune responses in hosts [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low biocontainment requirements for production; v. Ability to promote durable and robust humoral and cellular immune response [ 41 ]. Researchers have developed several novel adenoviral vectors for gene delivery, such as simian adenoviruses [ 26 ], human adenovirus type 4 (Ad4) [ 42 ], human adenovirus type 35 [ 43 ] (Ad35) vectors, and chimpanzee adenovirus type 68 (cAd68) [ 44 ]. Previous studies have demonstrated that these novel adenovirus vectors mediate the diverse immune responses in hosts [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2021, the recombinant COVID-19 vaccine (Adenovirus Type 5 vector) was approved by the National Medical Products Administration (NMPA) for SARS-COV-2 prevention [ 24 ]. However, pre-existing Ad5-neutralizing antibodies in the population have somewhat hampered its prospects as a human vaccine vector [ 26 ]. Adenoviruses are strictly species-specific, and animals do not naturally become infected with human adenoviruses.…”
Section: Introductionmentioning
confidence: 99%